1960
DOI: 10.1172/jci104111
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism and Fate of Tritiated Thymidine in Man *†

Abstract: The incorporation of thymidine (thymine deoxyriboside) into deoxyribonucleic acid (DNA) of proliferating cells has been studied in the past with various isotopic labels and biochemical techniques. Reichard and Estborn showed that thymidine-N15 was a specific precursor of DNA thymine in rats (1). Friedkin, Tilson, Roberts and Wood (2, 3) used thymidine-2-CI4 to show that this compound was incorporated into DNA thymidine of proliferating embryo and animal tissues with negligible partition of radioactivity into o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1

Year Published

1963
1963
1982
1982

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(59 citation statements)
references
References 14 publications
2
55
1
Order By: Relevance
“…Although the nuclear-cytoplasmic ratio of these cells appeared not to have changed, due to the morphologic alteration these cells were considered intermediary between a C or dispersed germinal center cells and immature cells of the plasma cell family. Rubini et al (1958) have studied the plasma and body clearance 3 of H -thymidine in man. The plasma is almost completely cleared of 3 H -thymidine in thirty minutes.…”
Section: Histology Of White Pulp Of Primary Immunized Animalsmentioning
confidence: 99%
“…Although the nuclear-cytoplasmic ratio of these cells appeared not to have changed, due to the morphologic alteration these cells were considered intermediary between a C or dispersed germinal center cells and immature cells of the plasma cell family. Rubini et al (1958) have studied the plasma and body clearance 3 of H -thymidine in man. The plasma is almost completely cleared of 3 H -thymidine in thirty minutes.…”
Section: Histology Of White Pulp Of Primary Immunized Animalsmentioning
confidence: 99%
“…After rapid injection of tracer dose_s of 3H-labeled TdR to human subjects, a ve~ rapid plasma clearance has been reported with a T~a of 1-2 rain and ~ ofapproximately 25 rain (91). Nlost ofthe injected TdR appeared to be metabolized to thymine, which was further broken down in the liver to fl-aminoisobutyfic acid and COz (26).…”
Section: Ph~macokinetics Of Thymidlnementioning
confidence: 99%
“…Nlost ofthe injected TdR appeared to be metabolized to thymine, which was further broken down in the liver to fl-aminoisobutyfic acid and COz (26). Between 30 and 80% of the radioactivity was recovered from the urine as ~H-water with only a small amount of aH-fl-aminoisobutyric acid (91). Within one min of injection, 3H-TdR appeared to be incorporated into newly formed DNA ofprollferadng cells (91).…”
Section: Ph~macokinetics Of Thymidlnementioning
confidence: 99%
See 1 more Smart Citation
“…The problem of pre¬ cursor specificity can be overcome by use of adenine-8-14C (Foote & KoefoedJohnsen, 1959) or especially thymidine-3H (Sirlin, 1958; Hupp, Austin & Murphree, 1961). Rubini, Cronkite, Bond & Fliedner (1960) found that all nuclear labelling occurred in less than 60 min following thymidine-3H in¬ jection and that by 90 (Sirlin & Edwards, 1958;Foote, 1959).…”
mentioning
confidence: 95%